Mapeamento de combustível vegetal para o manejo do fogo no interior do Parque Nacional de Ilha Grande - Pezenti , Tersio Abel (2024)
This study aimed to understand the dynamics of vegetative fuel accumulation for effective fire management in preventing wildfires within the Parque Nacional de Ilha Grande (IGNP). Besides, it sought to provide initial support to the management of the Nature Conservation Unit (NCU) for the application of prescribed burns, considering the ecological, socioeconomic, and cultural aspects through the Integrated Fire Management Plans (IFMPs). Physical vegetation samples were collected to measure the availability of wet and dry biomass, these data were compared with images obtained by a conventional Red, Green, Blue (RGB) camera installed on a Remotely Piloted Aircraft (RPA). The images were processed using photogrammetry software to generate orthomosaics and employ two vegetation indices: the Visible Atmospherically Resistant Index (VARI) and the Modified Photochemical Reflectance Index (MPRI). These indices, along with physical collections, facilitated the mapping, comparison, and verification of the availability and distribution of aerial organic matter suitable for burning during different seasons from February 2022 to February 2023 on Peruzzi and Grande islands. The results indicated that late fall, winter, and early spring are periods when vegetation has a higher availability of dry organic matter, making it more combustible, these periods are critical due to the combination of natural factors (such as frosts and droughts), artificial factors (the hydrological level of the Paraná River), and anthropogenic factors (presence of territory users), making it unfavorable for prescribed burns and increasing the risk of fire spread. Late spring, summer, and early autumn are more suitable for prescribed burn activities, during these periods, there is still dry vegetation, but with lower loads, with green aerial vegetation predominating. The collections and dehydrations showed that Grande Island, one year after being burned by a wildfire, had an 80.55% return of aerial biomass compared to Peruzzi Island, which has not burned in 18 years, the data obtained for wet and dry biomass on Peruzzi Island indicate slight oscillation with possible aerial biomass cycle over time without burning. Finally, it is advised to use RPA with geographical positioning correction systems such as Post-Processed Kinematic (PPK) or Real-Time Kinematic (RTK) in hard-to-access or wet areas.